Communal justice in the Andes of Peru The case of Calahuyo. Antonio Peña Jumpa, Fondo Editorial de la Pontificia Universidad Católica del Perú, Lima, 1998, 389 pp. - Mujica Bermúdez, Luis (1999)
The review does not present a summary.